1998
DOI: 10.1128/mcb.18.2.1029
|View full text |Cite
|
Sign up to set email alerts
|

POU Transcription Factors Brn-3a and Brn-3b Interact with the Estrogen Receptor and Differentially Regulate Transcriptional Activity via an Estrogen Response Element

Abstract: The estrogen receptor (ER) modulates transcription by forming complexes with other proteins and then binding to the estrogen response element (ERE). We have identified a novel interaction of this receptor with the POU transcription factors Brn-3a and Brn-3b which was independent of ligand binding. By pull-down assays and the yeast two-hybrid system, the POU domain of Brn-3a and Brn-3b was shown to interact with the DNA-binding domain of the ER. Brn-3-ER interactions also affect transcriptional activity of an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 78 publications
2
61
1
Order By: Relevance
“…27 Our initial studies in breast cancer cells, identified the BRCA-1 gene as a target for transcriptional repression by Brn-3b. 16 Hence, although Brn-3b can interact with the oestrogen receptor and enhance its ability to activate its target genes, 11 it appeared that Brn-3b might achieve its effects on the growth of breast cancer cells 19 by inhibiting rather than activating gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 Our initial studies in breast cancer cells, identified the BRCA-1 gene as a target for transcriptional repression by Brn-3b. 16 Hence, although Brn-3b can interact with the oestrogen receptor and enhance its ability to activate its target genes, 11 it appeared that Brn-3b might achieve its effects on the growth of breast cancer cells 19 by inhibiting rather than activating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…18 Moreover, Brn-3b has also been shown to interact with the oestrogen receptor via a protein-protein interaction and to enhance its ability to activate its target genes. 11 These findings suggest therefore, that the overexpression of Brn-3b in human breast cancer cells may act to modulate the growth of these cells by regulating the expression of specific genes with growth regulatory properties. In agreement with this idea, we have shown that overexpression of Brn-3b in the MCF-7 human breast cancer cell line results in increased growth rate, higher saturation density and enhanced ability to form colonies in soft agar, compared to the control empty vector transfected cells.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations